The impact of the French Tobin tax - Becchetti, L.; Ferrari, M.; Trenta, U. (Journal of Financial Stability, 2014)
We analyze the impact of the introduction of the French Tobin tax on the turnover and measures of the liquidity and volatility of the affected stocks with nonparametric tests on individual stocks, difference-in-difference tests and other robustness checks controlling for simultaneous month-of-the-year and size effects. Our findings indicate that the tax produces a significant reduction in turnover and volatility (measured in terms of stock price volatility and the high–low price range) and inconclusive effects on liquidity when the latter is evaluated under the two dimensions of the estimated bid–ask spread and the Amihud (2002) price impact ratio.